An in-vitro evaluation of Periotest(TM) implant stability measurements taken on implant retained crowns and healing abutments. - O'Brien, Cianna Marie (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2024)
This in vitro study aimed to assess the reliability of implant stability measurements recorded with the Periotest' device and to investigate the differences in values when these measurements were taken on implant retained crowns and healing abutments. To achieve our aims, implant stability measurements previously recorded by Naughton et al. (2023) for the same group of implants by using the ISQ Osstell' device, were used as a control and an attempt was made to correlate the PTVs to the ISQ values. The optimal position for placement of the Periotest' hand-piece on the implant abutment and crowns was also assessed. Finally, we sought to determine differences in implant stability for different implant systems and their possible effects on the Periotest' measurements. Seven different types of implants of similar length and width were placed in resin polyurethane blocks representing the four different bone densities (D1, D2, D3 and D4). Two blocks of each type of bone density were included in the study, resulting in a total of 56 implants of various design and connection type being placed in eight bone blocks. Implant abutments correlating to the implant manufacturer and connection type were attached to the implants to facilitate measurement of the implant stability and torqued to 5 N cm using a calibrated torque wrench. The Periotest' device was used to assess the implant stability at three different sites on the implant abutments - coronal, mid- and implant-head - with measurements repeated in triplicate. Screw-retained implant crowns designed to replicate an average central incisor were fabricated for each type of implant. The implant stability assessment was repeated on the implant-retained crowns following the same method of recording PTVs in triplicate, at three different heights on the crown. All measurements were repeated by a second operator and a total of 2,016 PTVs were recorded. Descriptive statistics were used to describe the PTVs recorded for the different implants in the bone blocks of different bone density. The PTVs obtained were compared to the ISQ values previously recorded by Naughton et al. (2023). The intraclass correlation coefficient (ICC) was used to determine the relationship between the PTVs recorded on the implant abutments and implant crowns. Further analysis involved plotting Blant Altman plots and the Wilcoxon Signed-Rank test. Spearman's rank test was used to assess the relationship between the PTVs recorded on implant abutments and ISQ values recorded for the same implants by Naughton et al. (2023). These analyses were repeated with D4 bone excluded. The ICC between operators was also calculated. Moderation analysis was used to investigate the effect of bone density and implant type on the implant stability measurements recorded. The range of PTVs was found to differ significantly in D4 bone blocks compared to bone blocks of D1-D3 bone density. The mean PTVs recorded when all bone densities were included was 5.32 +/- 11.493 PTV at the mid-abutment site and 11.96 +/- 12.264 at the mid-crown site. When D4 bone was excluded the mean PTVs were -0.82 +/- 3.050 at the mid-abutment site, and 5.36 +/- 3.843 at the mid-crown site. When compared to the Osstell' device, the Periotest' device was found to be reliable at assessing implant stability in all bone densities. A difference of 6 PTVs less stability (+ 6 PTV) for measurements recorded on implant crowns was found when compared to measurements recorded on implant abutments. This difference was found to be less consistent in D4 bone density. The intraclass correlation co-efficient between operators was good to excellent when assessing implant stability with the Periotest' device (ICC ranged from 0.776 to 0.938 for D1-D4 bone density, p <.001). The mid-abutment implant site was found to have the best correlation to the ISQ values (rs = -.482, p <.001) indicating that the mid-abutment site facilitated the most accurate assessment of implant stability using the Periotest' device. The results demonstrated that PTVs in the range of -5 to +5 correlated with ISQ values ? 60. For implants placed in good quality bone, some differences in implant stability measurements based on the different types of implants were identified. These results demonstrate that Periotest' is a reliable tool for the assessment of implant stability in all bone types. Measurements should be recorded at the mid-abutment site. The range of clinically acceptable implant stability for the Periotest' and Osstell' devices correlate well and there is a mean difference of about 6 PTV between measurements recorded on implant crowns compared to implant abutments for all bone densities. Finally, there were some differences in the implant stability measurements for different implant systems when these were placed in good quality bone. These differences didn't seem to have an effect on the reliability of Periotest' measurements.
APPROVED
Keywords: Periotest; implant stability measurements; primary stability; Osstell; periotest value; implant stability quotient; implant stability